Analysis of the current situation of Chinese culture communication among Thai Chinese learners - Pataburee, Tanakarn (Journal of Chinese Language and Culture Studies, 2023)
Thailand's "Chinese craze" has developed rapidly since its formation in 2003, and the number of people learning Chinese remains high. In recent years, with the spread of Chinese, the spread of Chinese culture in Thailand has also achieved certain results. Chinese culture is increasingly valued by Chinese learners. Based on literature analysis and survey interviews, this study designs a questionnaire to study the current situation of Chinese culture communication among Thai Chinese learners. This study also analyzes the problems and difficulties faced by Chinese culture communication in Thailand, and summarizes the Chinese culture of Thai Chinese learners by means of interview method. The present study show that the Chinese culture communication strategies of Thai Chinese learners can play a certain role in the overseas dissemination of Chinese culture.